Illustrated redescription of Haliplus (Liaphlus) arrowi Guignot, 1936 (Coleoptera: Haliplidae) from the Western Ghats, India, and notes on the closely related H. angustifrons Régimbart, 1892 - Sheth, Sayali D.; Ghate, Hemant. V.; van Vondel, Bernhard J. (Zootaxa, 2016)
In an ongoing survey of aquatic beetles, the crawling water beetles Haliplus (Liaphlus) arrowi Guignot, 1936 and Haliplus (Liaphlus) angustifrons Régimbart, 1892 were found only from four (three localities for H. arrowi and one locality for H. angustifrons) out of 85 localities sampled in and around the Western Ghats of Maharashtra. Digital images and scanning electron micrographs of diagnostic characters are provided for the first time for both the species. Intraspecific and interspecific variation in the elytral maculation of H. arrowi and H. angustifrons is illustrated.